The design of books and lives: Yiddish children’s Book Art by artists from the Kiev Kultur-Lige - Hoge, K (Legenda, 2016)
This chapter explores how visual signs of Soviet propaganda were entering the pages of children's books, increasingly occupying youngsters' minds, and how visual artists interpreted these symbols. The introduction and maturation of Soviet children's publishing was preceded by relatively new traditions of secular educational reading in Yiddish. In 1905, children's short stories by Sholem Aleichem and other Yiddish writers began to appear under the Warsaw imprint Bikher far ale. By 1920, the Soviet regime had been secured in Kiev which led to a dramatic change in Kultur-Lige's fortune: the organization was taken over by the Jewish Sections of the Communist Party and its publications slowly, almost reluctantly, started to adjust to a new ideological climate. Among Issachar Ber Ryback most famous creations were illustrations to poems by Leyb Kvitko, who in the 1930s became known as one of the most popular and well-published children's authors in the Soviet Union.